2018
DOI: 10.1088/1361-6560/aad9b6
|View full text |Cite
|
Sign up to set email alerts
|

Application of plastic scintillating fibres to surface dosimetry in megavoltage photon and electron beams: considerations for Cerenkov correction

Abstract: This work investigated the application of plastic scintillation detectors (PSDs) in dosimetry measurements on the surface of a phantom in megavoltage photon and electron beams. Emission spectra associated with fluorescence in the PMMA optical fibre, Cerenkov in the optical fibre, and the signal from the scintillator were characterized with a spectrophotometer. The angular dependence of the PSD response was studied with the PSD both in the plane and perpendicular to the plane of gantry rotation. Two methods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…However, it has been shown that Cerenkov will be produced in the scintillator itself. 8 To help understand how problematic the Cerenkov radiation could be in our SPSD, we have measured the directional dependence on the surface using a 16 MeV electron beam since this setup produces a relatively unidirectional beam of electrons which will, in turn, maximize the directionality of the Cerenkov emissions. The use of reflective tape in this setting is a first test of a simple correction strategy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has been shown that Cerenkov will be produced in the scintillator itself. 8 To help understand how problematic the Cerenkov radiation could be in our SPSD, we have measured the directional dependence on the surface using a 16 MeV electron beam since this setup produces a relatively unidirectional beam of electrons which will, in turn, maximize the directionality of the Cerenkov emissions. The use of reflective tape in this setting is a first test of a simple correction strategy.…”
Section: Discussionmentioning
confidence: 99%
“…At depth, electron scattering should result in more isotropic Cerenkov emission, resulting in a smaller directional dependence. 8…”
Section: B Spsd Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…a dose rate dependence less than 1%) [14,15,16], irradiation angle independence [13,14,15], high spatial resolutions [17,18] and real time responses [11,19]. PSDs have been used effectively for small field dosimetry [20,21,22] and in vivo dosimetry [23,24,25] with clinical LINACs. Given these qualities and their non-ferromagnetic composition, PSDs are promising 2 prospects for MRI-LINAC dosimetry.…”
Section: Introductionmentioning
confidence: 99%